Floria Cow-Calf and Stocker Beef Safety and Quality Assurance Handbook: Appendix - Todd A. Thrift; Matt J. Hersom; Max Irsik (EDIS)
AN174 includes pages 92-126 of the Florida Cow-Calf and Stocker Beef Safety and Quality Assurance Handbook, which is used for the voluntary Florida Beef Quality Producer program. It Includes several appendices to the handbook, including a glossary and several record sheets. Produced as part of a cooperative program by Florida Cattlemen's Association, Florida Department of Agriculture and Consumer Services, and the University of Florida (IFAS) Extension Service. Published by the UF Department of Animal Sciences, October 2006.